2018
DOI: 10.1108/jbim-10-2016-0236
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation – natural reward strategy linkage and its impact on sales performance: the mediating impact of salesmanship skills

Abstract: Purpose In the context of an emerging market, this paper empirically investigates the direct as well as the indirect impact of natural reward strategies (NRS) on the sales performance of B2B sales force. It also investigates the mediating impact of salesmanship skills on the NRS–sales performance linkage. Design/methodology/approach Structural equation modeling (using AMOS 18 software) is used to analyze the data collected, using a survey questionnaire from a sample of 317 B2B salespersons of a single media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…NRSL is “a cognitive strategy directed toward self and is a useful job resource for salespeople” (Singh et al , 2018, p. 354). As previously mentioned, although significant attention has been paid to TSL and NRSL, BSL has largely remained unexplored.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…NRSL is “a cognitive strategy directed toward self and is a useful job resource for salespeople” (Singh et al , 2018, p. 354). As previously mentioned, although significant attention has been paid to TSL and NRSL, BSL has largely remained unexplored.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Following the calls for more research in the area of self-leadership for salespeople (Verbeke et al , 2011), sales researchers have started to investigate the internal mechanisms through which a salesperson can be motivated to perform (Panagopoulos and Ogilvie, 2015; Singh and Venugopal, 2015). In addition, the identification of alternative methods of enhancing self-leading capabilities has gained scholarly attention (Singh et al , 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…So, the ability to regulate emotions during decision-making process is an important factor in goal accomplishment. For example, Singh et al (2018) found that salesperson's emotion regulation influences natural reward strategy, salesmanship skills and sales performance. Therefore, emotion regulation strategies maintain mental health (Kawata et al, 2019) and facilitate cognitive functioning (Tuicomepee et al, 2018).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Successful marketing strategies require companies to manage relationship between organizations and shape corporate boundaries (Chatterji et al , 2018); focus on the use of social media and use competitive intelligence, engagement and word of mouth to adjust the relationship between sales strategy and sales performance in a timely manner (Pham and Johnson, 2017); focus on the impact of cultural and social impacts on sales strategies (Micu et al , 2017); incentive salespeople through natural reward strategies (Singh et al , 2018), offer different commissions to salespeople for new products and remanufactured products and so on Kovach et al (2017); ensure that salespeople do not accept unrealistic and unsurpassed expectations from consumers (Rodriguez et al , 2018). It can be seen from the above that scholars mainly start from the external environment (Pham and Johnson, 2017), social environment (Micu et al , 2017), inter-organizational relationship (Chatterji et al , 2018), internal salesperson (Kovach et al , 2017; Singh et al , 2018) and consumers (Rodriguez et al , 2018). They used sentiment analysis (Micu et al , 2017), questionnaires (Singh et al , 2018; Pham and Johnson, 2017), text document analysis (Rodriguez et al , 2018) and other methods to study marketing strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the above that scholars mainly start from the external environment (Pham and Johnson, 2017), social environment (Micu et al , 2017), inter-organizational relationship (Chatterji et al , 2018), internal salesperson (Kovach et al , 2017; Singh et al , 2018) and consumers (Rodriguez et al , 2018). They used sentiment analysis (Micu et al , 2017), questionnaires (Singh et al , 2018; Pham and Johnson, 2017), text document analysis (Rodriguez et al , 2018) and other methods to study marketing strategies. In addition, this paper changes angle and method, we start with products, draw on game theory and use qualitative and quantitative methods to study sales strategies.…”
Section: Introductionmentioning
confidence: 99%